2022
DOI: 10.3389/fcvm.2022.927652
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metagenomic analysis of human intervertebral disc nucleus pulposus and cartilaginous end plates

Abstract: Study designThe diversity of microflora inhabiting endplate (EP) and nucleus pulposus (NP) tissues of human intervertebral disc (IVD) was profiled through NGS-supported 16S rRNA amplicon sequencing. Sixteen EP and their corresponding NP were excised from the brain-dead voluntary organ donors with no clinical history of low back pain, and 12 herniated and 8 degenerated NP tissues isolated from the patients undergoing spinal surgery were subjected to study the alteration in the microbial diversity.Objective(s)To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Lachnospiraceae and Ruminococcaceae belongs to Firmicutes . A metagenomic [ 40 ] study demonstrated a significant decrease in the abundance of Firmicutes , Actinobacteria , and Bacteroidetes in diseased discs. An animal study [ 41 ] found higher relative abundance of Lachnospiraceae and Ruminococcaceae and lower relative abundance of Lactobacillus in lumbar disc herniation (LDH) mice treated with Lactobacillus s16 .…”
Section: Discussionmentioning
confidence: 99%
“…Lachnospiraceae and Ruminococcaceae belongs to Firmicutes . A metagenomic [ 40 ] study demonstrated a significant decrease in the abundance of Firmicutes , Actinobacteria , and Bacteroidetes in diseased discs. An animal study [ 41 ] found higher relative abundance of Lachnospiraceae and Ruminococcaceae and lower relative abundance of Lactobacillus in lumbar disc herniation (LDH) mice treated with Lactobacillus s16 .…”
Section: Discussionmentioning
confidence: 99%
“…14,16,28,91,92 Disc herniations in most cases also disrupt the CEP because most herniations occur as avulsion type between the CEPs and bony endplate. 91,92 Consequently, endplate damage and herniations are seen as gate for bacterial entry to the disc (i.e., C. acnes), 93,94 which might lead to complement activation via the classical and alternative pathway in the disc 95 C. acnes are found in disc tissue, specifically in MC discs, but not in the BM. 37,96 Hence, it remains to be elucidated if (i) the complement system can be locally activated in disc, (ii) which complement factors are present in disc tissue, either through local production by disc cells or through influx from the BM, and (iii) if and how bacterialmediated complement activation in the disc also affects the MC marrow (Figure 3, Nr.…”
Section: Infiltration Of Bacteriamentioning
confidence: 99%
“…The persistence of pathological microbes harms the integrity of the intestinal barrier, mediating immune and mitochondrial failure. Even biomechanical disorders, such as intervertebral discopathies, seem to be associated with disc infection caused by oral and skin-derived pathogens ( Rajasekaran et al, 2020 ; Li et al, 2022b ; Shanmuganathan et al, 2022 ). Besides the aforementioned mechanisms, dysbiosis reduces the supply of calcium to the bone and impairs the ability to manufacture vitamins K2 and D and other important immuno-metabolic substances.…”
Section: Part Ii: Mitochondrial Dysfunction and Its Involvement In Di...mentioning
confidence: 99%